A Sustainable Method for the Synthesis of Acetic Acid Based on Dehydrogenation of an Ethanol–Water Solution Catalyzed by an Iridium Complex Bearing a Functional Bipyridonate Ligand. Issue 17 (28th May 2018) - Kuwahara, Masato; Nishioka, Masaaki; Yoshida, Masato; Fujita, Ken‐ichi
Abstract: An efficient system for the synthesis of acetic acid via dehydrogenation of an ethanol–water solution using a new iridium catalyst bearing a functional bipyridonate ligand with N, N ‐dimethylamino substituents was developed. Quantitative production of acetic acid from an ethanol–water solution was achieved. In addition, recovery and reuse of the catalyst using a simple procedure was also accomplished. Moreover, this catalytic system can be applied in the dehydrogenative transformation of various primary alcohols to the corresponding carboxylic acids. Abstract : The iridium life : An efficient system for the synthesis of acetic acid via dehydrogenation of an ethanol–water solution using a new iridium catalyst bearing a functional bipyridonate ligand with N, N ‐dimethylamino substituents has been developed. Quantitative production of acetic acid from an ethanol–water solution was achieved. This catalytic system can be also applied in the dehydrogenative transformation of various primary alcohols to their corresponding carboxylic acids.